Conceptual and Procedural Knowledge of Fractions Among Junior High School Students as Viewed through Cognitive Style - Yunda Devana Tiningsih; Subanji Subanji; Imam Rofiki; Siti Salina Mustakim (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
This study to describe the conceptual and procedural knowledge of junior high school students on fraction based on reflective and impulsive cognitive styles. This type of research is a descriptive with a qualitative approach. The research subjects were carried out by giving the MFFT Test to 68 prospective subjects, obtained 24 students with reflective cognitive style and 22 students with impulsive cognitive style. Furthermore, two subjects were selected from each category. Qualitative data collection regarding the conceptual and procedural knowledge aspects possessed by the subjects was carried out by providing fraction material test questions and interviews based on assignments. Data analysis uses data collection, data condensation, data presentation, and drawing conclusions/verification. The results showed that subjects with reflective cognitive style understanding of the five aspects of conceptual knowledge related to fractions, fractions as part whole, measurement, quotient, operator, and ratio. In the procedural knowledge, subjects with reflective cognitive style can use all four aspects in carrying out procedures related to fractions, verbalization procedures, applications fraction conversion, applications fraction operations and applications fraction simplification. While subjects with impulsive cognitive style tend not to understand conceptual and procedural knowledge of all aspects.